Combined action observation and imagery facilitates corticospinal excitability - Wright, David J.; Williams, Jacqueline; Holmes, Paul S. (Frontiers in Human Neuroscience, 2014)
Observation and imagery of movement both activate similar brain regions to those involved in movement execution. As such, both are recommended as techniques for aiding the recovery of motor function following stroke. Traditionally, action observation and movement imagery have been considered as independent intervention techniques. Researchers have however begun to consider the possibility of combining the two techniques into a single intervention strategy. This study investigated the effect of combined action observation and movement imagery on corticospinal excitability in comparison to either observation or imagery alone. Single-pulse transcranial magnetic stimulation was delivered to the hand representation of the left motor cortex during combined action observation and movement imagery, passive observation, or movement imagery of right index finger abduction-adduction movements or control conditions. Motor evoked potential (MEPs) were recorded from the first dorsal interosseous (FDI) and abductor digiti minimi (ADM) muscles of the right hand. The combined action observation and movement imagery condition produced MEPs of larger amplitude than were obtained during passive observation and control conditions. This effect was only present in the FDI muscle, indicating the facilitation of corticospinal excitability during the combined condition was specific to the muscles involved in the observed/imagined task. These findings have implications for stroke rehabilitation, where combined action observation and movement imagery interventions may prove to be more effective than observation or imagery alone.